2018
DOI: 10.3390/catal8120658
|View full text |Cite
|
Sign up to set email alerts
|

Combining Carbon Fibers with Ni/γ–Al2O3 Used for Syngas Production: Part A: Preparation and Evaluation of Complex Carrier Catalysts

Abstract: To promote the adsorption and activation of carbon dioxide in the dry reforming of methane (DRM), Ni and Al2O3 were coprecipitated on activated carbon fibers (ACF). Various characterization methods were adopted in order to investigate the surface characteristics of different catalysts. Chemisorption characterization results, such as H2-temperature programmed reduction (H2-TPR), H2-temperature programmed desorption (H2-TPD), and CO2-temperature programmed desorption (CO2-TPD) illustrated that ACF in a nickel-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In the case of AC catalyst supporter, one peak can be recognized at 660 C. Contrary, two adequately separated peaks are seen in case of metal loaded catalysts: one small peak at around 280 C and the main at 550 C. Yu et al demonstrate comparable results for Ni on AC fibers catalyst. 42 The intensities follow the Ni content at both peaks; however, a little temperature shift can be observed. The temperature of the maximum rate of reduction is decreased by increase the Ni content.…”
Section: Catalystmentioning
confidence: 96%
“…In the case of AC catalyst supporter, one peak can be recognized at 660 C. Contrary, two adequately separated peaks are seen in case of metal loaded catalysts: one small peak at around 280 C and the main at 550 C. Yu et al demonstrate comparable results for Ni on AC fibers catalyst. 42 The intensities follow the Ni content at both peaks; however, a little temperature shift can be observed. The temperature of the maximum rate of reduction is decreased by increase the Ni content.…”
Section: Catalystmentioning
confidence: 96%
“…Wei et al (2020) demonstrated that the carbon fiber with layered silicate could improve the sintering performance of the Ni-based catalyst at high temperature of CRM because carbon fiber favored the decomposition of CO 2 . Yu et al (2018) prepared Ni-based catalysts with different ratios of Al 2 O 3 /ACF for CRM reaction. They found that the incorporation of the activated carbon fibers (ACF) to the Ni/γ-Al 2 O 3 /ACF catalyst was beneficial to improvement of the CRM catalytic activity.…”
Section: Carbon Supportsmentioning
confidence: 99%
“…The conventional routes to employ biomass are diverse, including combustion to produce heat, pyrolysis to extract bio-oil, and gasification to obtain biogas [3]. Particularly under the background of rapid urbanization in China, converting biomass to biogas by means of gasification is of both social and economic significance, as it not only can supply centralized gas for urban residents, but also could largely reduce the dependence on fossil fuels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the issues of high CO content and low heating value, the biogas needs to be upgraded before it is finally transported to downstream users via pipelines. Water gas shift (Equation 1)is an efficient technical method to reduce the CO content in biogas, and the methanation reaction (Equation (2)) is able to increase the heating value by producing CH 4 . As a result, the above two reactions are frequently applied in the upgrading process of biogas into urban gas [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation